Expression of α‐glucosidase during morphological differentiation in the basidiomycetous fungus Pholiota microspora. (23rd April 2016) - Zhu, Gang; Hayashi, Mirai; Shimomura, Norihiro; Yamaguchi, Takeshi; Aimi, Tadanori
Abstract : The α‐glucosidase gene from Pholiota microspora, designated PnGcs, was amplified and characterized. The open reading frame region of PnGcs, from ATG to the stop codon, is 2937 bp and encodes a protein of 979 amino acids with a signal peptide of 20 amino acids at the N‐terminus. The predicted amino acid sequence of PnGcs indicated that it is a glycoside hydrolase family 31 protein. Quantitative reverse transcription PCR was used to investigate PnGcs expression in mycelia cultured in minimal medium containing various carbon sources, as well as in tissue during different stages of development of fruiting bodies. When P. microspora was grown in minimal medium supplemented with different carbon sources, PnGcs expression was highest when induced by maltose. During cultivation on sawdust medium, PnGcs expression increased dramatically at the fruiting body formation stage compared with the mycelial growth stage, which implied that PnGcs is closely associated with fruiting body development.